2020
DOI: 10.1002/htj.21682
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a magnetic field and Hall effects in nanoliquid flow under insertion of dust particles

Abstract: In this study, the two-phase hydromagnetic flow of a viscous liquid through a suspension of dust and nanoparticles is considered. The influence of the Hall current is also taken into account. The similarity variables are utilized to transform the problem into one independent variable. The obtained expressions in one independent variable are solved through the Runge-Kutta-Fehlberg scheme connected with the shooting procedure. The computed results are sketched for employing multiple values of physical constraint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The component forms of governing equations under boundary layer approximations are given by (see References [6,18])…”
Section: Mathematical Model Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…The component forms of governing equations under boundary layer approximations are given by (see References [6,18])…”
Section: Mathematical Model Of the Problemmentioning
confidence: 99%
“…They concluded that the temperature gradient increases with the fluid‐particle interaction aspect. Mahanthesh et al 6 investigated the magneto‐dusty nanofluid flow over an extending sheet with the Hall effect. They have employed the Maxwell nanoliquid model to simulate the enhancement in thermal conductivity of a dusty liquid due to nanoparticle (NP) insertion.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the effect of radiation on temperature was also studied 29 . In a very recent work, Mahanthesh et al 30 has presented the influences of magnetic and Hall parameters on a nanofluid flow with dust particles. Furthermore, the effect of a nonuniform heat source on a time‐dependent flow due to noncoaxial rotation has been analyzed by Mahanthesh et al 31 Shehzad et al 32 have presented the slip flow effect in a microchannel.…”
Section: Introductionmentioning
confidence: 99%
“…Siddiqa et al 10 addressed the heat transmission in a steady‐state dusty fluid past a radiating wavy cone. Some recent developments in modeling of a dusty fluid can be consulted through References [11‐15].…”
Section: Introductionmentioning
confidence: 99%